Pelatihan Pelayanan Pasien Dalam Bahasa Inggris Bagi Calon Tenaga Kesehatan Di Akademi Keperawatan Rumah Sakit Marthin Indey Jayapura: - - Budi Rahayu; Yohana Yembise; Asnita (J-Abdimas Cenderawasih, 2025)
This community service program aims to provide training to prospective healthcare workers at the Marthin Indey Hospital Nursing Academy (AKPER RSMI) in Jayapura in serving and managing English-speaking patients. Another objective of this community service program is to increase the motivation of AKPER RSMI students, as prospective healthcare workers, to learn English. This community service program took the form of training. The training included watching videos on working abroad as a nurse, lectures, discussions, and simulations. The training proceeded smoothly as planned. Participants received materials in the  lectures, then discussed the materials, and practiced them in simulations. In the final evaluation, participants felt they had benefited from the training and hoped to receive more similar training.